Evaluasi Penerimaan Aplikasi YouChat terhadap Pengalaman Belajar Mahasiswa PTN Surabaya menggunakan Model TAM - Lidya Bela Simarmata; Tri Lathif Mardi Suryanto (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2024)
With the rapid development of technology, its use has expanded to all sectors, including education. Artificial Intelligence (AI) plays an important role in providing innovative solutions, mimicking human intelligence, and potentially replacing human roles in several functions. In education, AI has proven to enhance learning motivation and active student participation. YouChat, an AI chatbot based on GPT-3.5, is used as a learning assistant offering features such as answering questions and providing idea suggestions. Observations and literature studies show that this application has great potential to improve students' learning experiences. This thesis aims to evaluate the acceptance of the YouChat application on students' learning experiences in public higher education institutions in Surabaya using the Technology Acceptance Model (TAM). Data were collected from 399 students and processed using the SEM-PLS technique with SmartPLS 3.2.9 software, including outer model, inner model, and hypothesis testing. The thesis results show that perceived enjoyment and perceived informativeness significantly affect attitude, which in turn affects the intention to use. The variable trust also moderates the effect of perceived informativeness on attitude. This thesis provides insights into students' acceptance of the YouChat application in their learning process as an evaluation for improvement, development, and enhancement for both YouChat and educational institutions.